Changing Maps: Cyberspace, Global Culture and the Interconnected Wor(l)ds of Geoff Ryman’s 253 - Esposito, Lucia (Margins/Marges/Margini, 2024)
The article focuses on the increasingly large and interconnected expanse of cyberspace, which is denoted by such a plurality of sites of cultural exchange and sharing between individuals and communities that it eludes mapping. Electronic literature, and in particular hypertext, with its malleability, interactivity, connectedness, indeterminacy, erosion of boundaries between nations, human and machine, public and private, seems best suited to making sense of our technologically textured and globalised reality. In this light, Geoff Ryman’s 253 is analysed as an experimental example of hypertextual and global narration; a locus where the evolving relationships between information technologies and social spaces, places and practices are staged and tested.